Mario Bellatin: ceremonies (El Taco en la Brea, 2022)
This work first narrates an episode caused by a very common procedure in Mario Bellatin's work, the parodic rewriting. In this case, the object of the parody is Literary Criticism (or literary critics), but at the same time, and in the foreground, the Japanese writer Yasunari Kawabata is honored. The second part is dedicated to highlighting other typical Bellatin narrative procedures, in particular his predilection for all forms of rituals and ceremonies.
Keywords: Mario Bellatin; narrative procedures; parodic rewriting; rituals; ceremonies